Dextrocardia: Clinical Vignettes - Ramesh Aggarwal; Shridhar Dwivedi (Indian Journal of Medical Specialities)
Dextrocardia is one of the rare cardiac positional anomalies, in which heart is located in the right side of thorax with its base-to-apex axis positioned to the right side. Dextroposition is different than dextrocardia where the heart is displaced to the right secondary to extracardiac causes like eventeration of diaphragm and right lung hypoplasia. The term situs solitus is used when heart and abdominal viscera are normally placed with the cardiac apex, spleen, stomach, and aorta are placed on the left side and inferior vena cava and liver placed on the right side, whereas situs inversus has mirror-image of the organs relative to their position in situs solitus. Dextrocardia, cardiac dextroposition, and situs inversus generally remain asymptomatic and are detected incidentally by imaging studies done for reasons other than cardiovascular system related problems. This article shares our experience of five cases of cardiac malposition that presented with atypical features of common medical problems. It highlights the importance of basic clinical examination in these patients which helps in making a bed side diagnosis of cardiac malposition and also prevents any mishap which can arise if any emergency intervention is done in patients of dextrocardia with or without situs inversus.